PENGARUH SIKLUS HIDUP PRODUK SEPEDA MOTOR HONDA TERHADAP STRATEGI PEMASARAN DI PT. ASTRA INTERNATIONAL TBK-HONDA DENPASAR - Putu Ayu Mitha Loka (Majalah Ilmiah Widyacakra, 2019)
Companies must pay attention to strategic steps in product evaluation, namely by conducting a study of the development of marketing by conducting a product life cycle analysis, because with the weak concept of marketing strategy will reduce the company’s sales volumr in the future. This research aimed to analyzed the influence of the life cycle motorcycle product on marketing strategy at PT. Astra International Tbk-Honda Denpasar. The sample of this research is 100 customers at PT. Astra International Tbk-Honda Denpasar. Data collection done by spread the questionnaire. The analysis technique used in this research was simple linear regression analysis, simple correlation analysis,t-test analysis and determination analysis. From the simple linear regression analysis test, the Product Life Cycle variabel (X) has regression coefficient equal to Y=1,85+1,01X that have positive effect to Marketing Strategy (Y) and the correlation coefficient of 0,8989, which means that the relationship between the product life cycle to the marketing strategy is very strong, this can be seen from the result of calculation t-count 20,31 > t-tabel 1,980. That’s meaning the product life cycle (X) has significantinfluence to marketing strategy (Y) at PT. Astra International Tbk-Honda Denpasar are acceptable. Based on determination test, the product life cycle has an influence to marketing strategy of 80,8% and the remaining 19,2% by other variabels not examinated in this research.